Bill of Lading
1938-02-01 030-0210-002 (3) 10,000 1/37 T.B. Ltd. Recommended by the Chamber of Shipping Documentary Committee. 30/12/24. 21/12/33. 23/10/36. [stamp] OUTWARDS CONTINENTAL STEAM BILL OF LADING. Authorised by THE LONDON SHORT SEA TRADERS' ASSOCIATION. Shipped in apparent good order and condition by CO-OPERATIVE WHOLESALE SOCIETY LTD. on board the Steamship or Vessel called the PLOVER and now lying in this Port the following goods, viz. The General Steam Navigation Company, Ltd. Address for Telegrams " GLYCONIC TELEX, LONDON". Telephone No. ROYAL 3200-7 EDITION H Regd trade mark 15, TRINITY SQUARE, LONDON, E.C. 3. 8 bags Sugar short shipped (2951 ) TWO THOUSAND NINE HUNDRED AND FIFTY ONE BAGS KEGS BOXES AND CASES as per margin. being marked and numbered as in the margin hereof (weight, contents brand, measure, number, quantity, quality and value unknown) to be delivered (subject to the terms and exceptions and with the liberties to call and/or discharge at any other port or ports as hereinafter mentioned) in the like good order and condition at the ship's rail where the ship's responsibility shall cease at the Port of HAVRE. or as near thereto as she may safely get, unto M. Edouard Agent of 101 Boulevard Strasbourg. Le havre. Freight, charges and primage to be paid by SHIPPERS at LONDON. .................................Shillings and.................................Pence Sterling per ton Gross Weight ................Pence Sterling per Cubic Foot ................Shillings and............Pence Sterling and disbursements including shippers' charges forward (if any) as per margin and any other sums payable hereunder or to be paid by Consignee at HAVRE. Rice- few small holes, few bags resewn Flour- few small holes, few bags wet staines Leading Distinctive No. of Quantity Gross Weight Marks No.s Packages Tons Cwts qrs lbs. N.C.L. BARCELONA 1/160 - 160 bags VIA HAVRE. Rice 16. 3. 0. 24. ................161/280 -120 bags lentils 6. -. -. -. 281/830 - 550 bags 34 17 1 8 Flour. ...............................051/861- 31 kegs Cocoa. 1.14. 1. 8. ..................862/948 - 87 Boxes Soap. 4. 18. 2. 17. ...................................949/951 - 3 Cases Meat Cubes. -. 6. 3.15. TLP N.C.L Barcelona Via Havre 2000 bags Sugar. 196.17.-. 1................... Particulars furnished by Shipper under Article III of the Rules :— No. of Packages as above. [stamped] Agents at Havre La Société de Consignation Maritime Franco-Britannique Rue Jules Siegfried Le Havre Value declared by Shipper under Article IV of the Rules ............£ [stamped] THE GOODS TO PAY FIFTEEN PER CENT. ON THE AMOUNT OF FREIGHT AND PRIMAGE FOR PLACING THE GOODS UNDER TACKLE AT HAVRE. FROM UNDER SHIPS TACKLE THE GOODS WILL BE SUBJECT TO CHARGES FOR HANDLING AS PER TARIFF OF THE UNION DES NEGOCIANTS TRANSITARES COMMISSIONAIRES DU HAVRE. Disbursements including Shipper's ) charges forward (if any). ) £-- And it is mutually agreed as follows :- 1. This Bill of Lading is and shall have effect subject to :— (a) The terms exceptions and immunities of the Carriage of Goods by Sea Act 1924, and of the Rules comprising the Schedule thereto all which are herein incorporated. To the extent that any term of this Bill of Lading is repugnant to or inconsistent with anything in the Rules it shall be void. (b) all statutory limitations of or exemptions from liability of carriers and/or ships, and (c) the terms and exceptions printed on the back hereof. 2. The Carrier is not and does not hold himself out to be a common carrier. He does not bind himself to despatch his ships at advertised times, or guarantee the sailing of any ship. 3. Freight, Charges and Primage : — (a) shall be deemed earned on shipment ; (b) shall be payable, ship or goods lost or not lost, and when paid shall not be repayable under any circumstances ; (c) shall be paid in full without any allowance, credit or discount. (d) The Carrier shall not be responsible for "Shipper's charges forward" in the event of goods being lost or refused by Consignee. 4. Parcels for different consignees collected or made up in a single package addressed to one Consignee shall pay full freight at the rate applicable to the highest rated parcel in the package. 5. In case any damage or loss results to the Carrier, ship, cargo, lighters, cranes or hoisting tackle owing to incorrect weight, or no weight, having been declared, or to improper packing or fastenings, the Shipper and/or Owner of the goods shall be responsible therefor. 6. The Goods may, at the Carrier's option and at the risk of the Consignee and/or Owner of the goods, be re-weighed, re-measured and/or examined at the place of loading or discharge and if the weight, measurement and/or description shown on this Bill of Lading be incorrectly stated, double freight on the correct weight, measurement and description of the goods shall be paid, and the cost of re-weighing, re-measuring and/or examination will be added to the freight and be payable before delivery of the goods. A certificate signed by the Carrier or his Agents shall be conclusive evidence of the correct weight measurement and description, and the freight payable thereon. 7. The Shipper and/or Owner of the goods shall bear and pay the cost of all mending, baling, cooperage, and repairs of packages, boxes, crates, wrappers, bags or barrels, resulting from insufficiency of packing or fastenings or from excepted perils. 8. The extra freight payable on goods, the value of which has been declared by the Shipper to exceed £100 per package or unit, has been based and calculated upon the description and value furnished by the Shipper, if such description or value has been misstated, the Shipper and/or Owner of the goods shall pay such freight as would have been charged by the Carrier if the goods had been accurately described and valued and a certificate, signed by the Carrier or his agents shall be conclusive evidence as to the amount that would have been so charged. 9. Lien. The Carrier shall have a lien over the goods for all freight, additional freight, primage, disbursements, expenses, charges, loss or damages of any kind whatsoever which under the provisions of this Bill of Lading are to be borne and paid bythe Shipper and/or Owner of the goods, and for the interest (if any) payable thereon, and for the costs and expenses of maintaining and exercising such lien. The Carrier shall also have a right to sell the goods or part thereof by public auction or otherwise and thereout to pay or retain the costs and expenses of maintaining and exercising such lien and of such sale and all the sums for which a lien is given to the Carrier hereunder. The Carrier shall also have a general lien on the goods in respect of any previously unsatisfied freight, primage and charges due to him in respect of other goods from, the Shipper or Owner of the goods or any or all of them. If on the sale of the goods, the proceeds fail to cover the amount for which the Carrier has a lien on the goods, and the costs and expenses of maintaining and exercising such lien and of the sale, the Carrier shall be entitled to recover the difference from the Shipper and/or Owner of the goods. 10. Cargo which is stated herein as being carried on deck and is so carried, and live animals, are received, kept, carried and discharged at the sole risk of the Owner of such cargo or animals, and the Carrier shall not under any circumstances of any kind whatsoever be liable for any loss of or damage or delay thereto, whether or not such loss, damage or delay may be due to the wrongful act, neglect or default of the Carrier or the Master, Pilot, Officers, Crew, Stevedore, Servant, Agent or other person whomsoever for whom the Carrier may be responsible, whether in the service of the Carrier or not, and whether or not the above-named ship or any other ship or craft in which the said cargo or animals may be loaded was unseaworthy at the time of loading or sailing or at any other time. 11. Dangerous Goods.—Shippers shall not ship on board or send down for shipment any goods of an inflammable, explosive, poisonous or otherwise dangerous nature without written permission. If any such goods be shipped or received the Owner thereof shall be responsible for any and all fines expenses, liabilities, loss, delay or damage sustained or incurred by the Carrier directly or indirectly either in respect of the ship or otherwise howsoever, or by the Owners of other goods, and the Carrier shall have a lien upon the goods for and until payment of all the said sums, and such goods may be seized and destroyed by the Carrier, at any time, without compensation being payable. 12. The words " Shipper and/or Owner of the goods " wherever used in this Bill of Lading shall include the Shipper, Consignee and/or Endorsee of the Bill of Lading, Owner of the goods, Receiver of the goods and/or Holder of this Bill of Lading whether by way of security or as Agent or otherwise, or the party or parties signing this Bill of Lading as agent or otherwise. 13. All claims arising under this Bill of Lading shall be determined according to British Law by the Courts of the United Kingdom to the exclusion of the jurisdiction of any other country. 14. In accepting this Bill of Lading the Shipper and/or Owner of the goods expressly accepts and agrees to all its stipulations, exceptions and conditions whether written, printed, stamped, or incorporated, as fully as if they were all signed by such Shipper and/or Owner of the goods. FOR THE GENERAL STEAM NAVIGATION CO., LTD [signed] [manuscript] As agents for the shippers In Witness whereof the Master or Agent of the ship has agreed this tenor and date, one of which being accomplished the others to stand void. [signed] Dated in.......LONDON. this 1st day of FEBRUARY. 1938 292/946/30/210(ii)